The rate and equilibrium constants for a multistep reaction sequence for the aggregation of superoxide dismutase in amyotrophic lateral sclerosis - Khare, Sagar D. (National Academy of Sciences, 2004)
Mutation-induced aggregation of the dimeric enzyme Cu, Zn superoxide dismutase 1 (SOD1) has been implicated in the familial form of the disease amyotrophic lateral sclerosis, but the mechanism of aggregation is not known. Here, we show that in vitro SOD1 aggregation is a multistep reaction that minimally consists of dimer dissociation, metal loss from the monomers, and oligomerization of the apo-monomers: [Formula: see text] where D(holo), M(holo), M(apo), and A are the holo-dimer, holo-monomer, apo-monomer, and aggregate, respectively. Under aggregation-promoting conditions (pH 3.5), the rate and equilibrium constants corresponding to each step are: (i) dimer dissociation, K(d) ≈1 μM; k(off) ≈ 1 × 10(–3) s(–1), k(on) ≈1 × 10(3) M(–1)·s(–1); (ii) metal loss, K(m) ≈0.1 μM, [Formula: see text] , [Formula: see text]; and (iii) assembly (rate-limiting step), k(agg) ≈1 × 10(3) M(–1)·s(–1). In contrast, under near-physiological conditions (pH 7.8), where aggregation is drastically reduced, dimer dissociation is less thermodynamically favorable: K(d) ≈ 0.1 nM, and extremely slow: k(off) ≈3 × 10(–5) s(–1), k(on) ≈3 × 10(5) M(–1)·s(–1). Our results suggest that familial amyotrophic lateral sclerosis-linked SOD1 aggregation occurs by a mutation-induced increase in dimer dissociation and/or increase in apomonomer formation.